The colonial gap: An analysis of income distribution in the Port of Dakar, 1911-1940 - Castillo Hidalgo, Daniel (Economic history of developing regions, 2024)
This study presents new empirical evidence on the structure of income of African workers in the Port of Dakar between 1911 and 1940. It provides a systematic series of public wages earned by the African and European workforce in a colonial seaport. This series includes income structure by skill tier of public employees and labourers employed at the port. Did wage structure evolve according to relative increases in human capital accumulation in this major colonial seaport? In this investigation, I use data collected from the annual budgets of the port to seek explanations for the structural differences in income in three consecutive decades between 1911 and 1940. I found that the skill premium between highly skilled and unskilled African workers was 3.8 on average during the period analysed. Moreover, the skill premium between mid-skilled and unskilled workers is estimated to be 2.7. Furthermore, top and senior European staff (less than 10% of the staff) accounted for 36% of the overall income. I provide quantitative evidence on how colonial allowances were the key element that contributed to the increasing income gap between European and African workers in similar job categories.